Resilience as an investigation of the relationship between architecture and nature - Valerio De Caro (ARSNET, 2022)
Recent research involving the architectural project seems to have brought attention to natural elements and phenomena, highlighting particular interest in the interpretation of the dynamic processes of the environment and of all its entities, plant and natural that inhabit it. In a logic of resilience, which should lead to limiting the consumption of resources, the action of replacing technological devices with natural mechanisms tested throughout natural history appears to be a losing battle right from the start. Yet man, in the past, has shown that he is able to give interpretations of nature that are not limited to a mechanistic replacement of the natural process, but which are based on the representation and reformulation of organisms in relation to matter and space. Space understood as an architectural essence, which from the relationship with nature gives back meaningful forms and experiences. The analysis of a series of case studies starting from the Lascaux caves up to the contemporary reinterpretations by Anton-Garcia Abril and Terunobu Fujimori demonstrate how nature can be an element of inspiration for innovative research in the field of design without necessarily embarking on a drift technological.